The Correlation between Emotional Intelligence and English Achievement of the 2015/2016 Fifth Semester English Literature Students of UIN Alauddin Makassar of UIN - Aswinda Darwis (Journal of Applied Linguistics, 2022)
This research is intended to find out whether or not there is a significant correlation between emotional intelligence and English achievement of the fifth semester students of English literature department of UIN Alauddin Makassar and to explore how the high, moderate, and low achiever students learn and engage in English. In conducting the research, the researcher used mixed method in which both quantitative and qualitative approach were applied. Emotional intelligence questionnaire by Goleman was administered to 33 students and their scores were correlated to their English achievement (GPA) by using Pearson correlation coefficient. Observation and interview were carried out to get more detailed information about how the high, moderate, and low achiever students learn and engage in English. The result revealed that there was significant correlation between emotional intelligence and English achievement of both the high and moderate achiever of the fifth semester students of English literature department of UIN Alauddin Makassar. While for the low achievers there was not significant correlation. In addition, the high, moderate, and low achiever students were different in learning and engaging in English. Key Words : Correlational Research, Emotional Intelligence, English Achievement